ANALYSIS ON THE USE OF WORKING CAPITAL PRODUCER COOPERATIVES AND KNOW TEMPE INDONESIA "Kopti" MUNICIPALITY IN YOGYAKARTA - Budiman, Diky; Murdo, Drs. Yuri; Darini, M.Si., Dra. Sri (Management, 2010)
Working capital is a property that is used to finance day-to-day company. Working capital is usually in the form of cash, receivables, inventories, all of which were included in the current asset balance sheet structure. The relationship of working capital dengankegiatan everyday very closely, for example, to purchase raw materials, bahanpembantu, salaries / wages of its employees must be present to support the activities of the company. Besides modalkerja have enough will benefit the company, with an efficient working capital are also companies will not experience losses. Based on the writer´s observation of production decline at the Cooperative Tofu and Tempeh Tofu and Tempe Manufacturer Indonesia (Kopti) in the Municipality of Yogyakarta from year to year (2006-2009) Based on analysis of activities, menunujukkan activities that are not stable. Assessment of working capital efficiency shown by the activity ratio menunujukkan assets decreased efficiency, but increases inventory efficiency, which in 2008 amounted to 207.8 x 92.5 x 2009. Keywords : working capital, producer cooperatives